Immune–Inflammatory Biomarkers Predict Cognition and Social Functioning in Patients With Type 2 Diabetes Mellitus, Major Depressive Disorder, Bipolar Disorder, and Schizophrenia: A 1-Year Follow-Up Study - Garés-Caballer, Marta; Sánchez-Ortí, Joan Vicent; Correa-Ghisays, Patricia; Balanzá-Martínez, Vicent; Selva-Vera, Gabriel; Vila-Francés, Joan; Magdalena-Benedito, Rafael; San-Martin, Constanza; Victor, Victor M.; Escribano-Lopez, Irene; Hernandez-Mijares, Antonio; Vivas-Lalinde, Juliana; et al. (Frontiers in Neurology, 2022)
Background Systemic, low-grade immune–inflammatory activity, together with social and neurocognitive performance deficits are a transdiagnostic trait of people suffering from type 2 diabetes mellitus (T2DM) and severe mental illnesses (SMIs), such as schizophrenia (SZ), major depressive disorder (MDD), and bipolar disorder (BD). We aimed to determine if immune–inflammatory mediators were significantly altered in people with SMIs or T2DM compared with healthy controls (HC) and whether these biomarkers could help predict their cognition and social functioning 1 year after assessment. Methods We performed a prospective, 1-year follow-up cohort study with 165 participants at baseline (TB), including 30 with SZ, 42 with BD, 35 with MDD, 30 with T2DM, and 28 HC; and 125 at 1-year follow-up (TY), and determined executive domain (ED), global social functioning score (GSFS), and peripheral blood immune–inflammatory and oxidative stress biomarkers. Results Participants with SMIs and T2DM showed increased peripheral levels of inflammatory markers, such as interleukin-10 (p < 0.01; η2p = 0.07) and tumor necrosis factor-α (p < 0.05; η2p = 0.08); and oxidative stress biomarkers, such as reactive oxygen species (ROS) (p < 0.05; η2p = 0.07) and mitochondrial ROS (p < 0.01; η2p = 0.08). The different combinations of the exposed biomarkers anticipated 46–57.3% of the total ED and 23.8–35.7% of GSFS for the participants with SMIs. Limitations Participants' treatment, as usual, was continued without no specific interventions; thus, it was difficult to anticipate substantial changes related to the psychopharmacological pattern. Conclusion People with SMIs show significantly increased levels of peripheral immune–inflammatory biomarkers, which may contribute to the neurocognitive and social deficits observed in SMIs, T2DM, and other diseases with systemic immune–inflammatory activation of chronic development. These parameters could help identify the subset of patients who could benefit from immune–inflammatory modulator strategies to ameliorate their functional outcomes.